Estimation of Equipotent Doses for Anti‐Inflammatory Effects of Prednisolone and AZD9567, an Oral Selective Nonsteroidal Glucocorticoid Receptor Modulator. (19th August 2020) - Almquist, Joachim; Sadiq, Muhammad Waqas; Eriksson, Ulf G.; Hegelund Myrbäck, Tove; Prothon, Susanne; Leander, Jacob
Abstract : AZD9567 is a potent and selective nonsteroidal oral glucocorticoid receptor modulator. It is developed as an anti‐inflammatory drug with improved safety profile compared with steroids like prednisolone. Throughout the clinical development of AZD9567, dose selection and data interpretation require a method for determining doses with the same anti‐inflammatory effect as prednisolone. Equipotent doses of AZD9567 and prednisolone were defined by the same average inhibition of TNFα release, a biomarker of anti‐inflammatory effect, measured in a lipopolysaccharide‐stimulated whole blood ex vivo assay. Based on pharmacokinetic‐pharmacodynamic models, TNFα dose‐response relationships for AZD9567 and prednisolone were established. A comparison of the dose‐response curves enabled estimation of an equipotency relationship. Specifically, 20 mg prednisolone was estimated to be equipotent to 40 mg AZD9567 (95% confidence interval: 29–54 mg). Static concentration‐response analyses showed that the relative potencies for inhibition of TNFα release of AZD9567 and prednisolone were well aligned with several other pro‐inflammatory cytokines.